Handloom industry on the way of exticntion: an empirical study over the pre-dominant factors - Ghosh, Suntu Kumar; Akter, Md. Shahriar (BRAC University, 2010)
Handloom industry in Bangladesh is having glorious past, questionable present and blurry future due to a lot of internal and external factors that are acting behind the scene. In this paper, we have identified those predominant factors that are moving the wheels of this industry slowly. And among them, shortage of working capital, high cost of raw material procurement, lack of organizing capability, inadequate technology and efficiency, and lack of policy support are major forces which are bitterly hit the handloom industry.